1983
DOI: 10.1104/pp.71.1.173
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Synthesis and Turnover of α-Amylase in Attached and Detached Cotyledons of Vigna mungo Seeds

Abstract: a-Amylase activity increased in attached cotyledons of germinated Vigna muago seeds until the 5th day after imbibition and decreased thereafter, whereas in detached and incubated cotyledons the activity continuously increased and, at the 6th day, reached the value more than three times that of the maximum activity of attached cotyledons. Zymograms of the activities and Ouchterlony double inmunodiffusion test on the activities of attached and detached cotyledons showed that the increase of activity in detached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…It has been documented that amylase production depends on the accumulation of a specific translatable mRNA (Higgins et al 1982;Koshiba and Minamikawa 1983), and that gibberellic acid (GA) induces the synthesis of new a-amylase mRNA (Muthukrishnan et al 1983). In barley and other cereals GA promotes the formation of protease and other hydrolases in addition to amylase (Yomo and Varner 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that amylase production depends on the accumulation of a specific translatable mRNA (Higgins et al 1982;Koshiba and Minamikawa 1983), and that gibberellic acid (GA) induces the synthesis of new a-amylase mRNA (Muthukrishnan et al 1983). In barley and other cereals GA promotes the formation of protease and other hydrolases in addition to amylase (Yomo and Varner 1973).…”
Section: Discussionmentioning
confidence: 99%
“…We used only detached cotyledons because of their high ability of a-amylase synthesis as described previously (7). Vigna mungo dry cotyledons detached from their embryonic axis were immersed in water for 6 h and then surface sterilized in 1% NaOCI solution for 5 min, rinsed with sterile water, and incubated under aseptic conditions for 4 or 5 d as described previously (7). The (14), and Jackson and Larkins (5).…”
Section: Methodsmentioning
confidence: 99%
“…Germinating seeds generally exhibit high amylase and protease activities. These enzymes were studied in some cereals, legume seeds (Koshiba and Minamikawa, 1983;Morohasi, 1986;Rahman et al, 2006). It was observed that protease activities present in dry seeds were enhanced during germination (Harvey and Oaks, 1974).…”
Section: Introductionmentioning
confidence: 99%